Happiness between appearances and pitfalls - Luzi, Michela (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Happiness can be imagined as the destination of an individual path, but also as the starting point towards a better existential dimension, more fulfilling, more attractive and hence more satisfying, which well represents the concept of flourishing. Human flourishing is well represented by the possibilities and opportunities for optimal functioning that connote virtue, productivity, growth and lead to the achievement of holistic well-being that is projected from the person into society, through a eudonic and eudemonic perspective.